GLOBAL TROPICAL CYCLOGENESIS - Sharkov, Eugene A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book presents the first physical findings of an investigation into the spatio-temporal characteristics of the global tropical cyclogenesis. Since Global Tropical Cyclogenesis was first published in 2001, many important scientific results have been obtained using methods and techniques developed by the author, including: the detection of the global tropical cyclogenesis as a main element of poleward heat transport in the terrestrial atmosphere; the evolution tropical activity in equatorial precipitable water fields; and scales of interactions between solar activity and global tropical cyclogenesis. These are all explained, together with the new scientific knowledge gained from the study of spatial-temporal properties of the global tropical cyclogenesis which affects satellite oceanography, atmosphere physics, ocean engineering, air-sea interaction and ocean remote sensing. Professor Sharkov gives findings from the Russian scientific airplane-based remote sensing expeditions to the Far East over the Pacific and the several scientific marine expeditions to the tropics as part of major research projects of the Russian Academy of Sciences. A principal feature of the book is the integrated description of spatial-temporal and structure properties of atmosphere catastrophes. Emphasis is placed on the physical aspects of breaking processes necessary to judge the possibilities and limitations of remote sensing methods in monitoring and mitigating natural hazards. The author includes numerous practice applications and illustrations taken from air-borne, ship-borne and laboratory up-to-date experiments. New chapters cover the possible impact of solar activity and effects of tropical cyclones on the upper atmosphere, time series and cumulative functions of global tropical cyclogenesis over 25 years, ionosphere and tropical cyclones activity, instability genesis in compress and saturated moist air atmosphere and complex satellite and in-situ "Scenario-TC" and "Global-RT" databases. A new Appendix gives quantitative data on spatio-temporal features of global and regional tropical cyclogenesis from 1983 to 2008.
Keywords: Geography; Physical geography; Meteorology; Climatic changes; Earth Sciences; Geophysics/Geodesy.; Meteorology/Climatology.; Geography (general).; Climate Change